O processo de capacitação para a produção enxuta: estudo de caso na Volvo do Brasil - Meirelles, Helena Teixeira (Universidade Federal de São Carlos, 2007)
Most companies attempting to implement Lean Manufacturing have focused only on the manufacturing process (tools and techniques) and have ignored the cultural aspects, essential to the change management process. This explains the partial success they have experienced in their efforts to become lean and is largely related to an inefficient qualification process, which were not enough to develop the competencies demanded by this production system. In order to understand better and to analyze how companies are qualifying their employees, this work has the objective to characterize and to analyze the qualification process developed by a company that has been going through a comprehensive lean transformation process. The characterization accomplished help us to understand how companies can qualify their employees in Lean Manufacturing System and how they can structure their qualification process in order to develop the competencies demanded by this paradigm. The analysis of the field research s results consisted in positioning the qualification process found against the studied theory, providing important insights about the direction future qualification activities should be addressed or about the way they should be drived. In the theory field, it is important to emphasize the contribution of the framework developed, which gathered and related different dimensions (critical elements) of Lean Manufacturing System, helping the investigation and analysis of the guidelines to the qualification process for this Production System.
Keywords: Administração da produção; Produção enxuta; Desenvolvimento de competências; Sistema Toyota de produção; Competência para melhoria contínua; Qualification process; Lean Manufacturing; competencies.; ENGENHARIAS::ENGENHARIA DE PRODUCAO